AB0413 Comparison of Interferon-γ Release Assay Versus Tuberculin Skin Test in the Golimumab Pursuit UC Program and the Golimumab SC Rheumatology (RA, PSA, and as) Program. (9th June 2015) - Hsia, E.C.; Schluger, N.; Cush, J.J.; Matteson, E.L.; Xu, S.; Sandborn, W.; Rutgeerts, P.; Marano, C.
Abstract : Background: Active TB is a significant safety risk associated with anti-TNF treatment. Screening & appropriate treatment for latent TB infection (LTBI) has been shown to substantially reduce the risk of developing active TB. Interferon-γ release assays (IGRAs) offer the possibility of an improved method to detect TB infections in pts with autoimmune disorders. Objectives: Compare results of an IGRA vs standard TST as a screening tool for LTBI in Golimumab (GLM) PURSUIT Ulcerative Colitis (UC) program vs.GLM SC Rheumatology (RA, PsA, AS) program 1 . Methods: In both programs, pts were screened for LTBI using standard TST & IGRA to assess eligibility in the following studies: PURSUIT-SC & PURSUIT-IV; GO-BEFORE, GO-FORWARD, GO-AFTER, GO-REVEAL, & GO-RAISE, resp. Any pt with a newly identified positive (pos) finding for TB in whom there was no evidence of active TB was permitted to enter provided appropriate treatment for LTBI was initiated before or at the time of first dose of study agent. TST was performed by Mantoux method, using 5TUs of PPD standard or 2TU of PPD RT-23. TST was deemed pos for LTBI per local country guidelines for an immunosuppressed host or, in the absence of local guidelines, according to an induration ≥5mm. The IGRA used to screen for LTBI was QuantiFERON-TB Gold In-Tube test. Overall IGRA & TST results were assessed. The impact of prior BCG vaccination & concomitant medications (ie corticosteroids &/or immunomodulators) on outcome was also assessed. Results: In GLM PURSUIT, 1283 pts & in GLM Rheum, 2282 pts had both IGRA & TST screening prior to GLM treatment. Both programs were global; differences were PURSUIT incl S. Africa & Rheum program incl Asia. In PURSUIT & Rheum programs, agreement between TST & IGRA results, measured by kappa coefficient, was 0.135 (95% CI, 0.050-0.220; p=0.028) & 0.22 (95% CI, 0.157-0.279; p=0.021), resp. Overall, in PURSUIT, 501 (39.0%) of 1283 pts had previously received BCG vaccine; among this vaccinated grp, the rate of pos for LTBI by TST was 10.4% vs 5.0% for IGRA pos. In Rheum program, 781 (34.2%) of 2282 pts had previously received BCG vaccine; within this vaccinated grp, the rate of pos for LTBI by TST was 15.2% vs 9.1% for IGRA pos. PURSUIT pts who had not received the BCG vaccine, the rate of pos by TST was 1.9% vs 2.8% for IGRA pos compared with 5.0%vs5.8%, resp, in the Rheum program. When IGRA was repeated in PURSUIT pts whose results were initially indeterminate, the majority of pts (67.0%) were IGRA neg on repeat whereas the number of pts whose results were pos was 5.3%; IGRA remained indeterminate for 27.7%. Similar results were seen in the Rheum program (74% IGRA neg, 2.7% pos, & 23.2% remained indeterminate). Concomitant corticosteroid &/or immunomodulator use did not appear to have an impact on results. Conclusions: Results of this comparison of IGRA and TST in the GLM PURSUIT & GLM Rheum programs suggest that IGRA provides greater specificity & possibly greater sensitivity than TST, & performs similarly in UC & Rheum populations. References: Hsia EC et al. A&R Vol. 64, No 7, July 2012 pp. 2068-2077. Disclosure of Interest: E. Hsia Employee of: Janssen R & D, LLC, N. Schluger Grant/research support from: Janssen R & D, LLC, J. Cush Grant/research support from: Janssen R & D, LLC, E. Matteson Grant/research support from: Janssen R & D, LLC, S. Xu Employee of: Janssen R & D, LLC, W. Sandborn Grant/research support from: Janssen R & D, LLC, P. Rutgeerts Grant/research support from: Janssen R & D, LLC, C. Marano Employee of: Janssen R & D, LLC